FACTORS AFFECTING REFRIGERATOR-FREEZERS ENERGY CONSUMPTION - R. Saidur Saidur; H.H. Masjuki; T.M.I. Mahlia; A.R. Nasrudin (ASEAN Journal on Science and Technology for Development, 2002)
Two frost-free household refrigerator-freezers, one with 492 liter capacity and one with 460 liter capacity were tested in the laboratory to determine the sensitivity of several variables those influence consumption refrigerator-freezers energy consumption greatly. The effects of single variables such as room temperature, thermostat setting positions, and door openings on the energy  consumption were investigated. Using Response Surface Methodology (RSM), a mathematical model has been developed to investigate the combined effect of room temperature, thermostat setting positions, and door opening on the energy consumption of refrigerator-freezers. From the mathematical model, it has been observed that room-temperature has the highest effect on the energy consumption followed by the thermostat setting position. The door opening has lowest on the energy consumption. More detailed tests were performed under different room temperature, thermostat setting positions, and door opening conditions and presented in this paper.